Kurt Klaudi Klausen and Annick Magnier (eds.). The Anonymous Leader. Appointed CEO s in Western Local Government, Odense: Odense University Press, 1998, 311 s., kr. 300,00. - Bruun, Finn (Politica, 1999)
-